How food policies emerge: The pivotal role of policy entrepreneurs as brokers and bridges of people and ideas. (August 2021) - Giambartolomei, Gloria; Forno, Francesca; Sage, Colin
Highlights: Integrated framework that combines policy entrepreneurship and collective leadership theories. Novel methodological approach merging embodied experiences and external observations. Focus on the phase of emergence of urban food strategies (UFS). Discussion on collective and relational practices of policy entrepreneurship. Local governance approaches should understand place leadership as key to initiate UFS. Abstract: Research has highlighted how new policy networks are transforming the food governance landscape, with pioneering urban governments addressing food security challenges through the adoption of what have been generically labelled urban food strategies (UFS). Yet within the literature on place-based food governance initiatives, the role and tactics of different stakeholder groups within these experiences remains insufficiently investigated. This paper seeks to fill the gap by shedding light on the complex dynamics entrenched in the establishment of inclusive UFS in two different but comparable civic initiatives: Cork (in the Republic of Ireland) and Bergamo (Northern Italy). The paper draws upon a unique multi-methods qualitative approach combining in-depth interviews and direct observations on the part of the lead author of the paper, with direct and embodied experience of the other two contributing authors. As the analysis reveals, policy entrepreneurship is best considered as a set of collective leadership practices that hold emancipatory potential, a key to accelerate the transition towards more just and sustainable food systems.